Investigating the Causal Relationships between Project Complexities and Project Cost: An Empirical Study from New Zealand - Linlin Zhao; Jasper Mbachu; Zhansheng Liu; Xuefeng Zhao; Bill Wang (Advances in Civil Engineering)
Project complexity is usually considered as one of the main causes of cost overruns, resulting in poor performance and thus project failure. However, empirical studies focused on evaluating its effects on project cost remain lacking. Given this circumstance, this study attempts to develop the relationship between project cost and the multidimensional project complexity elements. The study assumes complexity as a multidimensional factor including the task, organization, market, legal, and environment complexities. And it adopts an empirical evidence-based structural model to account for the relationships between project cost and project complexity. By doing so, a quantitative assessment of multidimensional project complexity has been developed. The findings suggest that task and organization complexities have direct effects on project cost, while market, legal, and external environment complexities have indirect effects on project cost. The practical contribution is that the findings can improve the understanding of which dimension of complexity significantly influences project cost and the need to focus efforts on strategically addressing those complexities.